Factors influencing the varietal preference of onion thrips, Thrips tabaci under storage conditions - Mala, B R Jayanthi; Jayanthi, P D Kamala; Nighot, Prathibha; Sankar, V; Mahajan, V (Indian Journal of Plant Protection, 2020)
Short Commucation